Characterization of backbending in even-even ¹²⁰⁻¹³⁰Te isotopes - Hussein, M.; Hossainc, I.; Mansour, S.A. (Вопросы атомной науки и техники, 2014)
In this paper, the nuclear structure of yrast bands of even-even ¹²⁰⁻¹³⁰Te isotopes has been described as a result of the backbending phenomena of moment of inertia. The square of rotational frequency, moment of inertia and fermi energy of those nuclei has been calculated from available experimental values. We have studied systematic moment of inertia, fermi energy as a function of even neutron number of ¹²⁰⁻¹³⁰Te isotopes. Moment of inertia as a function of the square of the rotational angular velocity for even neutron numbers from N = 68 to 78 in Te isotopes indicates the nature of backbending properties. The investigation of the backbending phenomena in ordinary space for even-even Te isotopes with even neutron number N = 68 to 78 are carried out and compared with gause space. Keywords: Moment of inertia; Te isotopes; Backbending; even-even nuclei; ground state band.